365 Arrival to Decision: Improving Waiting Times in Surgical Ambulatory Care. (4th May 2021) - Mahmood, F; Patel, P; Islam, O
Abstract: Introduction: An audit of the newly established Surgical Emergency Ambulatory Care Unit (SEAC) at Furness General Hospital found perceived patient waiting times were high. This Quality Improvement Project assessed the patient flow through the SEAC unit and aimed to improve the average time from arrival in the department to senior review by 10%. Method: The Plan Do Study Act (PDSA) methodology for quality improvement was used, the time from arrival in the unit to senior decision was recorded for each patient seen over one-week data collection periods. Analysis of the data allowed for a patient process map to be created to visualise bottlenecks in patient flow. The findings were discussed with all team members and an agreed intervention was implemented and tested. Results: Over three PDSA cycles, a significant improvement in the overall time from arrival to decision was achieved, from an average time of 193 minutes to 150 minutes. This was achieved by introducing a referral form, which altered how and when members of the multidisciplinary team communicated with each other. Conclusions: Clear communication at the appropriate time between all members of the SEAC team significantly improved the average time from arrival to decision.